De lo lineal a lo circular: análisis de patrones discursivos en la investigación colombiana del EFL - Torres-Martinez, Sergio (Diálogos Latinoamericanos, 2025)
This corpus-based study examines how Colombian EFL research represents an example of linear applied linguistics—an academic practice characterized by publishing papers with criticisms and diagnostics without providing real solutions. Using Agentive Cognitive Construction Grammar (AgCCxG) theory, I analyzed a corpus of 103 academic texts (905,265 words) to identify aspirational solver language (constructions that complain, criticize, postpone, or delay solutions) and reduced agentive roles among authors. The analysis revealed 6,116 instances of aspirational solver language (6.84 per 1,000 words) and 2,121 instances of reduced agency (2.24 per 1,000 words), with a moderate positive correlation (r = 0.36) between these linguistic features. The findings demonstrate how Colombian EFL research discourse systematically employs linguistic constructions that diagnose problems while diminishing author’s agency in solution implementation. This study contributes to our understanding of academic discourse patterns in applied linguistics and offers a framework for transitioning from linear to circular approaches in language education research.